1998
DOI: 10.1182/blood.v91.6.2152
|View full text |Cite
|
Sign up to set email alerts
|

A Common Human β Globin Splicing Mutation Modeled in Mice

Abstract: The βIVS-2-654 C→T mutation accounts for approximately 20% of β thalassemia mutations in southern China; it causes aberrant RNA splicing and leads to β0 thalassemia. To provide an animal model for testing therapies for correcting splicing defects, we have used the “plug and socket” method of gene targeting in murine embryonic stem cells to replace the two (cis) murine adult β globin genes with a single copy of the human βIVS-2-654 gene. No homozygous mice survive postnatally. Heterozygous mice carrying this mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 12 publications
2
31
0
Order By: Relevance
“…Mouse models of a severe and a moderate form of b-thalassemia that recapitulate the erythrocyte and tissue abnormalities found in human b-thalassemia major/intermedia as well as LDL-R knockout mice are currently available and could be used to generate doubleknockout mice. 58,59 CONCLUSIONS The survey of heterozygous FH in a geographic area such as the island of Sardinia with a high frequency of b -thalassemia, due to a single mutation of the b-globin gene, has indicated that b -thalassemia has an LDLlowering effect in heterozygous FH, comparable to that obtained with prolonged treatment with moderate doses of statins. On this basis, it is likely that FH heterozygotes carrying b -thalassemia trait have some protection against coronary atherosclerosis and premature CHD as reported in normocholesterolemic individuals carrying this trait.…”
Section: Mechanisms Of Ldl-lowering Effect Of B -Thalassemia In Hetermentioning
confidence: 93%
“…Mouse models of a severe and a moderate form of b-thalassemia that recapitulate the erythrocyte and tissue abnormalities found in human b-thalassemia major/intermedia as well as LDL-R knockout mice are currently available and could be used to generate doubleknockout mice. 58,59 CONCLUSIONS The survey of heterozygous FH in a geographic area such as the island of Sardinia with a high frequency of b -thalassemia, due to a single mutation of the b-globin gene, has indicated that b -thalassemia has an LDLlowering effect in heterozygous FH, comparable to that obtained with prolonged treatment with moderate doses of statins. On this basis, it is likely that FH heterozygotes carrying b -thalassemia trait have some protection against coronary atherosclerosis and premature CHD as reported in normocholesterolemic individuals carrying this trait.…”
Section: Mechanisms Of Ldl-lowering Effect Of B -Thalassemia In Hetermentioning
confidence: 93%
“…Nonetheless, these SCD models have been instrumental in improving our understanding of vascular [105] and pulmonary complications [106] and for evaluating potential treatments [107]. Similarly, multiple mouse thalassaemia models, with various human mutations, are available [108–116].…”
Section: Non‐antibody‐mediated Rbc Clearancementioning
confidence: 99%
“…Both b +/IVSII-654 knockin and BKO mice had a phenotype of b-thalassemia intermedia, which was consistent with the previous report. 2,15,16 The animals were placed in polystylene shoebox cages, and acclimatized in the vivarium with room temperature of 22-25 C and humidity of~55% for 7 days under 12/12 h dark/light cycle. They were fed regular chow containing 1.0% calcium and 0.9% phosphorus, and reverse osmosis (RO) water ad libitum.…”
Section: Animalsmentioning
confidence: 99%